Technical Efficiency for Tea Smallholder Farmers under UTZ Certification System in Sri Lanka: A Stochastic Frontier Approach - Hunuwala Malawarage Suranjan Priyanath; S.P. Premaratne; Amina Yoosuf; D. Maurice (SEISENSE Journal of Management, 2018)
The study aimed to identify the determinants of the technical efficiency of Smallholder Tea Farmers (STFs) under UTZ certification system in Sri Lanka by employing stochastic production frontier using a sample survey of 75 STFs supported by the UTZ programme conducted between January and March in 2016. The results showed that a small number of STFs (11.8 percent) were over 90 percent efficient and the level of efficiency was found to be negatively related to coefficients of UTZ certified STFs and positively related to number of years with the same plants. The results further showed the labor and fertilizer were the significant factors that determine the tea production of STFs.